IL-27 as a novel biomarker for pruritus in nodular prurigo and bullous pemphigoid - Wang, Yifei; Zhang, Xin; Teng, Yun Te; Shen, Chen (Frontiers in Immunology, 2024)
IntroductionBullous pemphigoid (BP) and prurigo nodularis (PN) are chronic pruritic skin diseases that severely impact patients’ quality of life. Despite the widespread attention these two diseases have garnered within the dermatological field, the specific pathogenesis, particularly the molecular mechanisms underlying the pruritus, remains largely unclear. Limited clinical sequencing studies focusing on BP and PN have hindered the identification of pathological mechanisms and the exploration of effective treatment strategies.MethodsTo address this gap, we collected a total of 23 peripheral blood mononuclear cell samples from BP and PN patients, as well as healthy controls, and performed RNA sequencing analysis. By integrating bioinformatics and machine learning techniques, we aimed to uncover the shared immune regulatory networks and pruritus-related mechanisms between BP and PN.ResultsOur study identified 161 differentially expressed genes shared between BP and PN, which were primarily enriched in immune activation and neural pathways, providing crucial molecular insights into the pruritus-related mechanisms of both diseases. Furthermore, using the machine learning algorithms of support vector machines and random forest, we pinpoint 7 crucial genes shared between the BP and PN databases. Among these, IL-27 emerged as a potential pivotal gene, as its mRNA expression levels strongly correlated with clinical parameters including pruritus scores, immunoglobulin E levels, and eosinophil counts. Validation experiments conducted on clinical samples from an additional 22 participants confirmed the upregulation of IL-27 expression in both BP and PN lesions.DiscussionThis study is the first to unveil the shared inflammatory and immune pathways common to BP and PN, highlighting the critical role of IL-27 in the pathogenesis of these conditions. Our findings not only enhance the understanding of the intricate relationship between BP and PN, but also provide a foundation for the development of novel therapeutic strategies targeting these two dermatological conditions.